Adjustable Strabismus Surgery: An Early Glance - Farman Khan, Sana Nadeem B.A Naeem (Pakistan Journal of Ophthalmology, 2018)
Purpose: To assess the short term success rate of adjustable suture technique on rectus muscle strabismus surgery in terms of postoperative alignment Study Design: Prospective, interventional study Place and Duration of Study: Eye Department, Fauji Foundation Hospital, Rawalpindi, from 25th June, 2016 to 25th December, 2017 Material and Methods: We carried out a study using the fornix approach for adjustable squint surgery, in mainly horizontal strabismus in adults and cooperative children, to finely tune the postoperative alignment. The preoperative deviation, strabismus type, patterns, were measured and analyzed. The early postoperative alignment was measured at 6 weeks postoperatively, to assess the success of the adjustable suture technique. A sliding noose knot was used to adjust the sutures, 1 hour postoperatively under topical proparacaine anesthesia, after the effects of general anesthesia had worn off. Results: 31 patients were included in this study. The majority were female being 23 (74.5%). The age ranged from 9 to 37 years, with the mean age 16.87 ± 5.5 years. All consenting adults and teenagers, with strabismus were included in this study and operated via the adjustable suture technique. The mean preoperative deviation was 49.38 ± 16.29 ? prism diopters, and the mean postoperative deviation was 3.5 ± 5.42? prism diopters. The difference between the two was statistically significant (p < 0.05), using the Wilcoxon Signed Ranks test (p = 0.000). Early surgical success defined as alignment within ± 10? (prism diopters) of orthotropia at the end of 6 weeks after surgery, was found in 27 (87.1%) of our strabismus cases. Conclusion: Adjustable strabismus surgery is associated with excellent short-term postoperative outcomes in terms of alignment and patient satisfaction. Adjustable sutures should be considered in all strabismus cases, whether adults or children. Key Words: short term, success, adjustable, strabismus, fornix approach, alignment.